Gender Dimension of Social Capital and its Effects on Rural Household Welfare in Osun and Ondo States, Nigeria (2012)
Social capital is trust and willingness to live by the norms of one’s associates. This household welfare asset has the potential to break the poverty cycle. However, there is little evidence on gender sensitivity of the effect of social capital on welfare status in Nigeria. Hence, gender dimension of social capital and its effects on rural household welfare in Osun and Ondo states, Nigeria were investigated. A multistage random sampling technique was employed for the study. Osun and Ondo states were selected from the six states in Southwestern Nigeria. Eight Local Government Areas (LGAs) were selected from each state. Thereafter, five communities were selected from each LGA. Three hundred and seventy respondents were selected from all the communities based on probability proportionate to size. Data were collected using structured questionnaire on socio-economic characteristics and social capital dimensions; group and network; trust and solidarity; Social Cohesion and Inclusion (SCI); collective action and cooperation; Information and Communication (IC); and Empowerment and Political Action (EPA). Attendance at associations’ meetings is the number of times present on monthly basis. The mean per capita household expenditure was used as a proxy for welfare. Data were analysed using descriptive statistics, multiple and Tobit regressions at p= 0.05. Male Headed Households (MHH) constituted 51.3%. Mean age of MHH and Female Headed Households (FHH) was 44.1 ± 2.2 and 42.3 ± 1.2 years respectively. The mean household size was 6.2 ± 2.3 and 5.1 ± 1.4 for MHH and FHH respectively. Average meeting attendance by both sexes was two out of five. Density of membership index in association was 0.30 and 0.34 for MHH and FHH respectively. MHH had 0.73 index of participation while FHH had 0.58. FHH were more involved in IC (0.69) compared with MHH (0.46). The SCI index was 0.47 for MHH and 0.65 for FHH. Male household heads had higher EPA (0.67) compared with FHH (0.21). On the average MHH participated in three of five decision- making and two for FHH. Monthly cash contributions of male and female heads were N895.90 ± N55.37 and N985.67 ± N72.11 in 2007 respectively. Monthly average labour contributions for MHH and FHH were 2.4 ± 0.3 and 3.2 ± 0.1 mandays respectively. There was no significant difference between MHH monthly per capita expenditure (N2, 936.67 ± N143.43) and FHH (N3, 221.82 ± N104.10). Aggregate social capital enhanced welfare of MHH and FHH by 0.503 and 0.681 respectively. Meeting attendance reduced welfare for both sexes by 0.258. Participation in decision- making increased welfare of MHH and FHH by 0.714 and 0.812 respectively. Increase in household size reduced welfare for both sexes by 0.782. Increase in age reduced welfare of MHH and FHH by 0.225 and 0.319 respectively. Increase in level of education increased welfare of MHH (0.123) and FHH (0. 913) indicating that female benefit more. Social capital influenced welfare of female headed households more. Participation in decision- making, and level of education enhanced households` per capita expenditure. Household size, meeting attendance and age negatively affected households’ welfare.